2020
DOI: 10.6004/jnccn.2020.7603
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exercise on Chemotherapy Tolerance and Survival in Early-Stage Breast Cancer: A Nonrandomized Controlled Trial

Abstract: Background: Available preliminary evidence is conflicting on whether exercise can positively influence antineoplastic treatment tolerance and in turn improve survival. Patients and Methods: This study compared chemotherapy treatment tolerance and survival among women receiving adjuvant chemotherapy for early-stage breast cancer who participated in a single-arm trial of supervised aerobic and resistance exercise programming versus a historical cohort that did not receive structured exercise programming. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…Besonders relevant ist der Aspekt der Therapieverträglichkeit. Ein gezieltes Trainingsprogramm kann dem Patienten relevante Vorteile für den Behandlungsplan schaffen und ein reduziertes Risiko einer Dosisreduktion erbringen [19].…”
Section: Ziele Der Bewegungstherapieunclassified
“…Besonders relevant ist der Aspekt der Therapieverträglichkeit. Ein gezieltes Trainingsprogramm kann dem Patienten relevante Vorteile für den Behandlungsplan schaffen und ein reduziertes Risiko einer Dosisreduktion erbringen [19].…”
Section: Ziele Der Bewegungstherapieunclassified
“…however, find significantly less dose adjustments for regimens containing doxorubicin in the exercise group (35). Nonetheless, in the reported studies chemotherapy completion was a secondary outcome.…”
Section: A C C E P T E Dmentioning
confidence: 79%
“…This was corroborated by a more recent analysis by Mijwel et al (32) of the OptiTrain study, in which no beneficial effect of aerobic nor resistance training on chemotherapy completion was found. Also, Kirkham et al (34) found no difference in frequency of dose adjustments for the total sample of breast cancer patients in their nonrandomized study comparing combined strength and endurance exercise with historical controls who received care as usual. They did, however, find significantly less dose adjustments for regimens containing doxorubicin in the exercise group (34).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is still a leading cause of death worldwide and the incidence and mortality is growing rapidly due to the increased life expectancy and lifestyle issues [36].The complexity of breast cancer development and the recurrence of this disease spur the researchers for developing new targets for breast cancer diagnosis and treatment [37][38][39]. Previous studies have shown that TRPM7 might be considered as a potential target for breast cancer treatment [29].…”
Section: Discussionmentioning
confidence: 99%